SYNTHESIS AND CHARACTERIZATION OF COPPER HEXACYANOFERRATE (II) NANOPARTICLES - Nguyễn, Đình Trung (2022)
Nanoscale copper hexacyanoferrate (CuHF) is a low-cost material prepared via a chemical co-precipitation method. XRD diagram, FTIR spectrum, EDS image, HR-TEM image, surface area (BET), and pore volume parameters were used to determine the properties and morphologies of the CuHF. The synthesized nanomaterials have the following properties: nanoscale and cubic structure (space group F-43m). The CuHF molecular formula was Cu13[Fe(CN)6]14·(2K)·10H2O. CuHF was a complex substance with a surface area of 12.80 m2/g and average pore width of about 34.50 nm.